Ghana : Report on the Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2004)
This report on the Observance of Standards and Codes on Fiscal Transparency Module on Ghana highlights a fiscal transparency module. Ghana meets the standards of the fiscal transparency code in several areas. In spite of the progress, the transparency of fiscal activities still falls short of the standards in a number of important areas. A strong commitment from the authorities to further strengthen fiscal transparency remains therefore essential. The transparency of the budget preparation process could be improved.